Optimizing Motivation in Purchase Decision-Making for MOSSDOOM Products on the Shopee App - Sabrina Noor Wijaya; Nabila Zahara; Nanda Nurul Atika; Nurlaila Nurlaila (Proceeding International Conference on Islamic Economics Community Services (ICIECS), 2023)
E-commerce has experienced rapid growth in recent years, transforming consumer shopping patterns from traditional methods to online shopping. Mossdoom, a local fashion brand that has seen significant growth in 2023-2024, has successfully attracted consumer attention through high-quality bags at affordable prices on e-commerce platforms such as Shopee. However, the lack of optimal understanding of factors influencing consumer purchasing motivation poses challenges for Mossdoom in enhancing sustainable purchasing decisions. This article employs deep interview and collaboration methods to identify the factors affecting consumer motivation in purchasing Mossdoom products. The findings indicate that consumer motivation, including needs, online shopping convenience, and reviews from other buyers, significantly influences purchasing decisions. By leveraging marketing strategies based on an understanding of consumer motivation, Mossdoom can enhance the appeal of its products on the Shopee e-commerce platform. The training provided to business actors and consumers successfully increases understanding of the importance of motivation in purchasing decisions and provides valuable insights for developing more effective marketing strategies. This article suggests that Mossdoom strengthen its brand image, optimize product presentation, leverage positive reviews, and collaborate with influencers to achieve sustainable sales growth.